GMOs in the Internal Market: New Legislation on National Flexibility. Issue 2 (March 2016) - Lee, Maria
Abstract : In an area where until now national autonomy has been tenaciously resisted, new EU legislation provides Member States with 'flexibility to decide whether or not they wish to cultivate GMOs on their territory'. This forces attention on to the subtle, and not so subtle, ways in which internal market law constrains political actors in the EU. But it is similarly suggestive of how political actors might contribute to the evolution of the internal market. As well as exploring this relationship between the new legislation and internal market law, this article reflects on the ways in which lessons from the past have been addressed by legislators. Whilst it takes somewhat seriously the politics of GMOs, the new legislation simultaneously reinforces some of the limitations of our dominant models for generating knowledge, including the EU's problematic dichotomy between facts and values, risk assessment and risk management.